Electrochemical properties of Fe(II) spincrossover complexes in different spin states: an investigation through electrochemical impedance spectroscopy - Hassan, H. C.; Said, S. M.; Hasnan, M. M.I.Megat; Zakaria, R.; Ibrahim, N. M.J.Nik; Fadzallah, I. A.; Noor, N. L.Md; Abdullah, N.; Noor, I. M. (Springer Science and Business Media Deutschland, 2025)
A method based on electrochemical impedance spectroscopy (EIS) was employed to investigate the charge transport mechanisms and electrical parameters of [Fe(Ln)2](BF4)2, with varying ligand lengths (Ln = L12, L14, and L16), that is [Fe(L12)2](BF4)2 (complex 1), [Fe(L14)2](BF4)2 (complex 2), and [Fe(L16)2](BF4)2 (complex 3) in an electrochemical redox solution. The spincrossover (SCO) phenomenon, which involves a transition between high spin (HS) and low spin (LS) states via the central metal ion was analysed under various external stimuli, including temperature changes, applied pressure, light irradiation at specific wavelengths, and/or magnetic field. The investigation revealed that the HS state of complex 1 exhibited the higher conductivity at room temperature (5.17 × 10−3 S cm−1) and with temperature dependence, attributed to its higher charge concentrations (n). Besides, the HS state of complex 1 showed a higher dielectric permittivity (εr) due to increased charge carrier polarisability at the electrode/electrolyte interface. Lower values of real (Mr) and imaginary (Mi) electrical modulus for the HS state of complex 1 suggested a more effective response of charge carriers to the applied electric field and faster charge carrier movement, leading to reduced relaxation time. The shift of the loss tangent peak of complex 1 towards lower frequencies during the spin state transition to the LS state indicated an increase in relaxation time, slowing down charge carrier movement and consequently decreasing ionic conductivity. These findings demonstrate the significant influence of spin state transition on the charge transport mechanism and electrical parameters of the SCO Fe(II) complexes.